2011
DOI: 10.3928/01477447-20111021-08
|View full text |Cite
|
Sign up to set email alerts
|

Navigated Total Hip Arthroplasty Using a 3-D Freehand Ultrasound System: Technical Note and Preliminary Results

Abstract: Ultrasound-navigated cementless total hip arthroplasty (THA) was performed in 10 consecutive patients with primary osteoarthritis of the hip between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Parratte and colleagues confirmed the high measurement accuracy of 1 mm with a hand-guided ultrasound transducer during registration of the anterior pelvic plane on human cadavers (Parratte et al 2008). By comparing ultrasound and pointer registration in the clinical implementation of a hip navigation system, Hirschmann et al reported deviations in the median acetabulum anteversion of 6° (range, 3°-13°) and in the median inclination of 3° (range, −1°-5°) for ultrasound registration as compared to pointer registration (Hirschmann et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Parratte and colleagues confirmed the high measurement accuracy of 1 mm with a hand-guided ultrasound transducer during registration of the anterior pelvic plane on human cadavers (Parratte et al 2008). By comparing ultrasound and pointer registration in the clinical implementation of a hip navigation system, Hirschmann et al reported deviations in the median acetabulum anteversion of 6° (range, 3°-13°) and in the median inclination of 3° (range, −1°-5°) for ultrasound registration as compared to pointer registration (Hirschmann et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…However, the associated hardware has excessive costs, and the calibration procedures increase operative time [ 16 ]. Finally, recent studies evaluating the use of intraoperative fluoroscopic imaging to optimize component position have shown significant improvements when performing THA [ 6 , 17 , 18 , 19 , 20 , 21 ]. However, manual acquisition and interpretation of these images present challenges in an intraoperative setting, including variability in the radiographic acquisition technique and complex geometric formulas to assess the 3D position of the cup from the 2D fluoroscopic image obtained [ 6 , 17 , 18 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%